The Multi-criterion Relay Technology of Power Distribution System Based on GOOSE - Jianhua Liu; Qiwei Zang; Dong Wang; Peng Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
GOOSE network of intelligent substation provides the fast packet transmission channel for the substation automation system, each IED connected in the GOOSE network can choose as subscribers or publishers to receive or publish data in order to achieve the station information sharing and equipment interoperability. In this paper, a 10kV bus protection scheme is proposed by combining intelligent substation requirements and the technical characteristics of the GOOSE protocol. This scheme uses intelligent substation information sharing and it is an application of GOOSE technology. A single-phase ground protection scheme is also proposed. It’s based on the GOOSE technology. Fault information is in GOOSE message, so all the IEDs can share it through the bay layer network .At last, this paper proposes the execution scheme for upgrading the traditional protection. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3742